Aplikasi Pengenalan Pondok Pesantren Al-Fatah Lias Baru Sebagai Sarana Promosi Menggunakan Adobe Flash Professional CS6 - utami, Dwi andrian; yanti, Risma; wati, Dharma (Universitas Harapan Medan, 2023)
With the development of the times, many technologies are increasingly sophisticated, and some technologies make it easier for people to access information. This also affects various promotions, from making advertisements, brochures, posters, and animations, to applications whose developments are now very versatile. Advertising media is often used in business and educational institutions. In the field of business, promotion is used to increase the success of product sales. However, in educational institutions, promotions are used to attract students to want to study in institutions that have been built. One example is promoting the Al-Fatah Lias Baru Islamic boarding school, a pesantren that introduces the facilities and advantages of Islamic boarding schools. One example of a promotion is made in the form of an animation-based application. The method used in making animation is the Motion Tween method using Adobe Flash Professional CS6. The results in this study are in the form of applications that can be accessed through computer devices with the Windows operating system.